2001
DOI: 10.3758/bf03196159
|View full text |Cite
|
Sign up to set email alerts
|

Richer color experience in observers with multiple photopigment opsin genes

Abstract: Traditional color vision theory posits that three types of retinal photopigments transduce light into a trivariate neural color code, thereby explaining color-matching behaviors. This principle of trichromacy is in need of reexamination in view of molecular genetics results suggesting that a substantial percentage of women possess more than three classes of retinal photopigments. At issue is the question of whether four-photopigment retinas necessarily yield trichromatic color perception. In the present paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(100 citation statements)
references
References 83 publications
2
94
2
1
Order By: Relevance
“…Studies of natural and laboratory experiments in color vision have historically been undertaken in concert, leading to complementary insights about both the genes that encode color photopigments and the variations in them that lead to colorblindness and color anomalies (Jameson, Highnote & Wasserman, 2001;Pickford, 1951).…”
Section: Genetic/environmental Factorsmentioning
confidence: 99%
“…Studies of natural and laboratory experiments in color vision have historically been undertaken in concert, leading to complementary insights about both the genes that encode color photopigments and the variations in them that lead to colorblindness and color anomalies (Jameson, Highnote & Wasserman, 2001;Pickford, 1951).…”
Section: Genetic/environmental Factorsmentioning
confidence: 99%
“…1,10,11 It is known that men and women differ in their capacity to distinguish shades, 7,12,13 and traditionally women have been considered better at selecting shades than men. 11,14 The majority of studies have attached little or no importance to the observer's gender at the time of shade selection, even though this is a variable that can influence the end result of the selection process. 8,12,13 Another variable to consider in shade matching is the observer's clinical experience, which can alter the capacity to reproduce the matching process.…”
Section: Introductionmentioning
confidence: 99%
“…Some estimates suggest four-photopigment females represent up to 50% of the female population; 8% of males are presumed to have four-photopigment retinas (Neitz et al 1998). Their study suggested that women with four-photopigment retinas perceived more chromatic bands in the typical rainbow spectrum than either men or women with trichromatic retinas (Jameson et al 2001).…”
Section: What Colors Do Animals See?mentioning
confidence: 99%
“…Even though half of the X chromosomes in a female become inactivated, if this is random in relation to the allele on the X for LWS, heterozygous females will have patches of cones with one or the other of the LWS photopigments. Behavioral studies have found that these females can detect more colors than females or males that are trichromatic (Jameson et al 2001). The two different LWS alleles also means that trichromatic males and females will differ in their perception of red light, depending on which LWS allele is on the X chromosome.…”
Section: Genetics Of Human Color Visionmentioning
confidence: 99%